Oxygen beams for therapy: advanced biological treatment planning and experimental verification. (20th September 2017) - Sokol, O; Scifoni, E; Tinganelli, W; Kraft-Weyrather, W; Wiedemann, J; Maier, A; Boscolo, D; Friedrich, T; Brons, S; Durante, M; Krämer, M
Abstract: Nowadays there is a rising interest towards exploiting new therapeutical beams beyond carbon ions and protons. In particular, 16 O ions are being widely discussed due to their increased LET distribution. In this contribution, we report on the first experimental verification of biologically optimized treatment plans, accounting for different biological effects, generated with the TRiP98 planning system with 16 O beams, performed at HIT and GSI. This implies the measurements of 3D profiles of absorbed dose as well as several biological measurements. The latter includes the measurements of relative biological effectiveness along the range of linear energy transfer values from ≈20 up to ≈750 keV μ m −1, oxygen enhancement ratio values and the verification of the kill-painting approach, to overcome hypoxia, with a phantom imitating an unevenly oxygenated target. With the present implementation, our treatment planning system is able to perform a comparative analysis of different ions, according to any given condition of the target. For the particular cases of low target oxygenation, 16 O ions demonstrate a higher peak-to-entrance dose ratio for the same cell killing in the target region compared to 12 C ions. Based on this phenomenon, we performed a short computational analysis to reveal the potential range of treatment plans, where 16 O can benefit over lighter modalities. It emerges that for more hypoxic target regions (partial oxygen pressure of ≈0.15% or lower) and relatively low doses (≈4 Gy or lower) the choice of 16 O over 12 C or 4 He may be justified.